Samuel Kimball, Charter, Other Powers, and Ordinances of the City of Lawrence (1866) Page 149, § 10 - (:unkn) unknown (General Publisher, 1863)
Prohibited the concealed carry of any pistol, Bowie-knife, or other deadly weapon. Violators fined not less than one nor more than ten dollars.
--
Keywords: CARRY - CONCEALED